Pengembangan Soal Evaluasi Berbasis Wordwall Terhadap Hasil Belajar Siswa Materi Perkalian Bilangan Cacah Dikelas 3 SD - Siti Asmawati Saekoni; Rifa’atul Mahmudah; Iwan Usma Wardani; Atiaturrahmaniah Atiaturrahmaniah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The study was to create a problem using wordwall and to evaluate its impact on the learning achievement of class iii students in round numerical materials. The background of this study is based on the problem of students' low interest and motivation in following the traditional mathematical learning assessments through the issues written in the package book. These circumstances leave many students feeling bored, diminished in zeal, even resulting in a decline in their study. The methods used in the study are research and development (randd) with addie models, consisting of analysis, design, development, implementation, and evaluation. The subject of this study is 20 students from class iii at the islamic school tahfidz darul mujahideen n majidi. The instruments used include a validation sheet from materials and media experts, a teacher and student response questionnaires, and pre-test and post-test results. The results from research indicate that it was a very valid t-wall evaluation, with the validation score of materials by 96.92% and media experts by 90.6%. In terms of practicality, the teacher's response is very positive, reaching a percentage of 96%, while the students give a positive assessment of this media by a percentage of 90%. In terms of effectiveness, there is seen an average increase in students' grades from 50 on pre-test to 85 on post-test. N-gain value by 0.7 shows a high category, which means wordwall use has proved to be effective in improving learning. Thus, the study asserts that development on wordwall assessments can be an innovative alternative to improved learning assessments, especially in elementary school numerical multiplicity.